Alefacept Promotes Immunosuppression‐Free Renal Allograft Survival in Nonhuman Primates via Depletion of Recipient Memory T Cells. Issue 12 (24th October 2013) - Lee, S.; Yamada, Y.; Tonsho, M.; Boskovic, S.; Nadazdin, O.; Schoenfeld, D.; Cappetta, K.; Atif, M.; Smith, R.‐N.; Cosimi, A. B.; Benichou, G.; Kawai, T.
Abstract Renal allograft tolerance has been achieved in MHC‐mismatched primates via nonmyeloablative conditioning beginning 6 days prior to planned kidney and donor bone marrow transplantation (DBMT). To extend the applicability of this approach to deceased donor transplantation, we recently developed a novel‐conditioning regimen, the "delayed protocol" in which donor bone marrow (DBM) is transplanted several months after kidney transplantation. However, activation/expansion of donor‐reactive CD8+ memory T cells (TMEM) occurring during the interval between kidney and DBM transplantation impaired tolerance induction using this strategy. In the current study, we tested whether, Alefacept, a fusion protein which targets LFA‐3/CD2 interactions and selectively depletes CD2highCD8+ effector memory T cells (TEM) could similarly induce long‐term immunosuppression‐free renal allograft survival but avoid the deleterious effects of anti‐CD8 mAb treatment. We found that Alefacept significantly delayed the expansion of CD2high cells including CD8+ TEM while sparing naïve CD8+ T and NK cells and achieved mixed chimerism and long‐term immunosuppression‐free renal allograft survival. In conclusion, elimination of CD2high T cells represents a promising approach to prevent electively the expansion/activation of donor‐reactive TEM and promotes tolerance induction via the delayed protocol mixed chimerism approach.